Building the tagset for Croatian - Stojanov, Tomislav (Array, 2008)
There is a number of morphological generators for Croatian language such as Kržak (1988), Silić (1996), Tadić (1994, 2003), and others that are parts of Korektor© , Hrvatska Riječ© , Lapis© and other applications, all of which, except Tadić's, have application as spelling checkers. Tadić's GenOblik is developed for the need of the corpus linguistics project and annotated according to the Multext-East specification (Erjavec 2001) that Przepiórkowski & Woliński (2003a, b) have critically evaluated having adopted their own tagset closer to grammatical system of Polish language. This paper also approaches from the criticism of the stated specification, but based on a different ground. The following is emphasized: (i) insufficient differentiation of inherent and relational motivated morphosyntactic features - verb relational categories such as modality, conditionality and compound tense cannot be annotated by tag that is added to an individual lexical unit - the stated features (in Croatian as well as in other languages) do not derive from form as such but are relationally conditioned. (ii) lack of adherence from morphosyntactic criteria in establishing formal criteria - semantic features, like the category of common and proper noun, are introduced, whereas other semantic categories, like countability and collectiveness, are not included. Tagging system that would rely on more emphasized qualitative approach is an issue of the second part of the work. The aim of the own tagging system is in the assumption that more grammatical adequacy could contribute to greater accuracy in solving homography in parser algorithm that is to follow. The tag system designed by Stojanov (2003) annotates the units from Silić's Grammar Thesaurus© , licensed by Microsoft and built into its Office application as a spelling checker for Croatian language. Arguments for its selection, and not for selection of some other morphological generator, are also given. Apart from being completed and fully functional, it is structured according to grammatical criteria. Thereupon, the 'overgenerating' effect is decreased maximally with high morphological well-formedness.